Meningkatkan Pengetahuan Digital Branding UMKM Berbasis Food And Beverages Kelurahan Klampis Ngasem Melalui Pelatihan - Fachmi Nursyamsi; Bowo Santoso (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
Product branding is a methodology in worldwide contests that generates plans, brand images and impressions that appeal to shoppers. The easiest thing that can be done for product branding is through a decent and attractive catalog photo. However, MSMEs that have not been able to take advantage of product branding are an obstacle for business actors in RW 09 Klampis Ngasem Village in developing their market. Most MSMEs are on average aged 40 and over which is of course very difficult to get involved in using marketing in digital business models. On this basis the community service carried out on Jl. Klampis Sacharosa, Kelurahan Klampis Ngasem by students from group 76 KKN-Thematic UPN "Veteran" East Java conducted counseling and training on branding. This activity resulted in new innovations for MSMEs in Klampis Ngasem Sub-District in the form of product photos according to standards and making Whatsapp Business which aims to facilitate the sale of MSMEs products in Klampis Ngasem Sub-District and is able to improve partners' ability to do branding. Through the use of digital branding as a marketing medium, the products produced can be recognized by more people and have greater opportunities to expand existing markets.